THE POTENTIAL OF REGIONAL GOVERNMENT FOR THE RATIONALIZATION OF LOCAL INFORMATION SYSTEMS (LE POTENTIEL OFFERT PAR UN GOUVERNEMENT REGIONAL DANS LA RATIONALISATION DES SYSTEMES D'INFORMATIONS LOCAUX) - Brown , J. Nicholas (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
see pdf